2009
DOI: 10.2203/dose-response.09-005.puskin
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on the use of LNT for Radiation Protection and Risk Assessment by the U.S. Environmental Protection Agency

Abstract: ᮀ The U.S. Environmental Protection Agency (EPA) bases its risk assessments, regulatory limits, and nonregulatory guidelines for population exposures to low level ionizing radiation on the linear no-threshold (LNT) hypothesis, which assumes that the risk of cancer due to a low dose exposure is proportional to dose, with no threshold. The use of LNT for radiation protection purposes has been repeatedly endorsed by authoritative scientific advisory bodies, including the National Academy of Sciences' BEIR Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
0
39
0
1
Order By: Relevance
“…Uranium mining has been linked to human cancers. It was mentioned in a report that depleted uranium compounds cause human cell transformation to the neoplastic phenotype [92]. A paper has mentioned many studies related to reproductive toxicity in humans and animals from uranium or depleted uranium exposure [93].…”
Section: Discussionmentioning
confidence: 99%
“…Uranium mining has been linked to human cancers. It was mentioned in a report that depleted uranium compounds cause human cell transformation to the neoplastic phenotype [92]. A paper has mentioned many studies related to reproductive toxicity in humans and animals from uranium or depleted uranium exposure [93].…”
Section: Discussionmentioning
confidence: 99%
“…There is little epidemiological evidence to support statistically significant radiogenic risks below 100 mSv (National Research Council 2005, Mossman 2006, Puskin 2009). The major source of risk data used in radiation protection is the Japanese Life Span Study (LSS).…”
Section: A Science (Risk Assessment) Perspectivementioning
confidence: 99%
“…Continuing the debate on a scientific basis is not likely to be fruitful because the science is not robust enough to support one theory to the exclusion of others. Current science cannot determine the existence of a dose threshold, a key piece to resolving the matter scientifically (National Research Council 2005, Puskin 2009). An alternative approach is to look at the LNT debate as a policy question and analyze the problem from a social and economic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Although cytostatic effects of low dose ionizing radiation have been reported (2,5,6,10), there is no consensus about the definition of a low dose and the safety limit for a cumulative dose. In BEIR VII (Biologic Effects of Ionizing Radiation) study, low dose radiation (<100 msv) was found not to increase the malignancy risk, but doses over 100 msv increase the overall cancer risk by 1% per 100 msv (14). Thus radiation safety should be provided for both the patient and the surgical team.…”
Section: Introductionmentioning
confidence: 99%